Broncholithiasis: From the Age of Aristotle to the Era of Surgical Pathology - Hartley, Christopher; V. Regenmorter, Adam; Rao, Nagarjun (Current Respiratory Medicine Reviews, 2016)
Broncholithiasis is a rare pulmonary condition caused predominantly by erosion of calcified perihilar and mediastinal lymph nodes into the bronchial lumen. The condition presents clinically in myriad ways including expectoration of stones, persistent cough, hemoptysis, pneumonia, obstructive respiratory failure, bronchoesophageal fistula or even massive hemorrhage. The clinical, radiographic, bronchoscopic and gross features have the potential for a mistaken diagnosis of bronchogenic carcinoma. Calcification of peri-hilar and mediastinal lymph nodes is most often caused by chronic granulomatous infections, particularly Mycobacterium tuberculosis and Histoplasma capsulatum. The stones act as nidus for colonization or superinfection with other microorganisms including Actinomyces spp. and Aspergillus spp. Bacterial, fungal, and mycobacterial special stains and microbiologic culture are essential in the work up of broncholithiasis.
Keywords: superinfection